Eisinsel "T-3" Post über Grönland - Müller, Gerhard (Handbuchfolge der Polarphilatelie e.V., 1986)
Includes short history and application of Ice Island T-3, lists all its activity period and names of all leaders in charge of operations. Details postal arrangements for the enterprise, the supply lines, and collaboration with U.S. Forces. Details various station cachets, postmarks of various places and periods, including misprints. Text is in German